2011
DOI: 10.1007/s10551-011-0916-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Phronetic Organization: The Case of Photographs in CSR Reports

Abstract: Aspects of phronetic social science and phronetic organization research have been much debated over the recent years. So far, the visual aspects of communicating phronesis have gained little attention. Still organizations try to convey a desirable image of respectability and success, both internally and externally to the public. A channel for such information is corporate reporting, and particularly CSR reporting embrace values like fairness, goodness, and sustainability. This study explores how visual portray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 65 publications
4
67
0
1
Order By: Relevance
“…A normative fit is exhibited, for instance, through the material and visual aspects of dress codes (e.g., Rafaeli & Pratt, 1993). Due to their ability to connect divergent elements inconspicuously in spatial arrangements, visuals can create 'legitimacy spillovers' (e.g., Benford & Snow, 2000;Haack, Pfarrer, & Scherer, 2014;Kostova & Zaheer, 1999) from familiar, socially shared and already institutionalized values and ideologies (e.g., modern working standards) to the new and/or potentially problematic (e.g., new employment laws), and are, therefore, uniquely suited to increase the familiarity and comprehensibility required for cognitive legitimacy (e.g., Höllerer et al, 2013;Rämö, 2011). The same is true for illegitimacy spillovers, when objects are brought in relation to illegitimate objects or practices (e.g., de-legitimating abortion practices through horrifying imagery) (e.g., Lefsrud, Graves, & Phillips, 2013).…”
Section: Visualitymentioning
confidence: 99%
“…A normative fit is exhibited, for instance, through the material and visual aspects of dress codes (e.g., Rafaeli & Pratt, 1993). Due to their ability to connect divergent elements inconspicuously in spatial arrangements, visuals can create 'legitimacy spillovers' (e.g., Benford & Snow, 2000;Haack, Pfarrer, & Scherer, 2014;Kostova & Zaheer, 1999) from familiar, socially shared and already institutionalized values and ideologies (e.g., modern working standards) to the new and/or potentially problematic (e.g., new employment laws), and are, therefore, uniquely suited to increase the familiarity and comprehensibility required for cognitive legitimacy (e.g., Höllerer et al, 2013;Rämö, 2011). The same is true for illegitimacy spillovers, when objects are brought in relation to illegitimate objects or practices (e.g., de-legitimating abortion practices through horrifying imagery) (e.g., Lefsrud, Graves, & Phillips, 2013).…”
Section: Visualitymentioning
confidence: 99%
“…In other works, métis, the Greek term for cunning, is described as resourcefulness, an ability to respond to demands, using maneuvers (Mackay, Zundel, & Alkirwi, 2014), or seeking to gain advantages regardless of truth (Roos, 2017). Rämö (2011) finds a connection between phronesis and responsibility. The author suggests that images that makeup CSR reports support the claims of responsibility and practical wisdom, illustrating organizations' activities not only in terms of financial results, but also in terms of socially and environmentally responsible action.…”
Section: Empirical and Theoretical Articles On Phronesis In Adminismentioning
confidence: 99%
“…Studies on the use of photographs in ARs concluded that they not only improved aesthetic appearance but also served rhetorical purposes (Graves et al ., ; Preston et al ., ; Davison, ). The rhetorical use of imagery in corporate social responsibility reporting has been found to minimise potential reputational damage related to bad news or to enhance reputation (Ihlen, ; Rämö, ). Breitbarth et al .…”
Section: Conceptual Underpinningmentioning
confidence: 99%